Comparison of xylazine and medotomidine as premedicants for cats being anaesthetised with propofol-sevoflurane - Selmi, A. L.; Mendes, G. M. [UNESP]; Lins, B. T. [UNESP]; Figueiredo, J. P.; Barbudo-Selmi, G. R. (Wiley, 2005)
The effects of premedicating cats with saline, xylazine or medetomidine before anaesthetising them with propofol-sevoflurane were compared. Twenty-four cats were randomly assigned to three groups of eight to receive either 0.25 ml of saline, 0.50 mg/kg of xylazine or 0.02 mg/kg of medetomidine intravenously, and anaesthesia was induced with propofol and maintained with sevoflurane. Medetomidine produced a greater reduction in the induction dose of propofol and fewer adverse postoperative effects than saline or xylazine. Hypoxaemia was observed after induction with propofol in the cats premedicated with saline and xylazine, but not in the cats given medetomidine. The cats treated with medetomidine and xylazine developed profound bradycardia. The blood pressure of the cats premedicated with saline and xylazine decreased, but the blood pressure of the cats premedicated with medetomidine was maintained. The cats premedicated with saline took longer to recover from anaesthesia than the other two groups.
Keywords: medetomidine; propoabbott; propofol; sevoflurane; virbaxyl; xylazine; alpha adrenergic receptor stimulating agent; ether derivative; hypnotic sedative agent; anesthesia induction; anesthetic recovery; bradycardia; breathing rate; cat; controlled study; diastolic blood pressure; dose response; drug dose reduction; female; general anesthesia; heart rate; hypoxemia; hysterectomy; nonhuman; oxygen saturation; premedication; randomization; systolic blood pressure; animal; animal disease; blood pressure; comparative study; drug effect; ovariectomy; time; Adrenergic alpha-Agonists; Anesthesia, General; Animals; Blood Pressure; Cats; Female; Heart Rate; Hypnotics and Sedatives; Hysterectomy; Medetomidine; Methyl Ethers; Ovariectomy; Preanesthetic Medication; Propofol; Time Factors; Xylazine